2019
DOI: 10.3329/bpj.v22i1.40021
|View full text |Cite
|
Sign up to set email alerts
|

In vivo Neurological, Analgesic and In vitro Antioxidant and Cytotoxic Activities of Ethanolic Extract of Leaf and Stem Bark of Wedelia chinensis

Abstract: Wedelia chinensis is a widely used anti-inflammatory and hepatoprotective medicinal plant in Bangladesh. In this study, analgesic, neurological, antioxidant and cytotoxic activities of the ethanolic extract of leaf and stem bark of W. chinensis were investigated. Oral administration of the ethanolic extract of W. chinensis (200- and 300-mg/kg body weight) was investigated on animal model for neurological activity using open field test and hole cross test. Acetic acid induced writhing method was used to assess … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Herb./GUBH/2018/97 dated on 11/10/2018). After the collection of plants, the fresh plants were washed and dried at room temperature for 2-3 weeks [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…Herb./GUBH/2018/97 dated on 11/10/2018). After the collection of plants, the fresh plants were washed and dried at room temperature for 2-3 weeks [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…The International Association for Study of Pain defines pain, as 'an unpleasant sensory and emotional experience associated with actual or potential tissue damage (Tadiwos et al, 2017). The substance which alleviates painful sensation by elevating the threshold to external stimuli is defined as an analgesic (Khanum et al, 2019). Non-steroidal anti-inflammatory drugs (NSAIDs), opioid analgesics and co-analgesics such as corticosteroids, neuroleptics, benzodiazepines, local anaesthetics, capsaicin and clonidine are the commonly used analgesics (Sriraj et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Non-steroidal anti-inflammatory drugs (NSAIDs), opioid analgesics and co-analgesics such as corticosteroids, neuroleptics, benzodiazepines, local anaesthetics, capsaicin and clonidine are the commonly used analgesics (Sriraj et al, 2018). Regular use of NSAIDs causes adverse side effects such as inflammation of gastrointestinal tract, renal failure and liver toxicity (Khanum et al, 2019). Studies have shown that opiate analgesics cause physical dependence, tolerance and addiction (Hijazi et al, 2017).…”
Section: Introductionmentioning
confidence: 99%